2003
DOI: 10.1161/01.cir.0000046447.72402.47
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Vitamin C Modify Monocyte and Endothelial Dysfunction in Young Smokers

Abstract: Background-Endothelial dysfunction initiated by monocyte-endothelial interactions has previously been observed in many vasculopathies, including chronic cigarette smoking. Taurine, a semiessential amino acid, and vitamin C, a naturally occurring antioxidant, have previously been shown to have endothelial protective effects when exposed to proinflammatory insults. Therefore, we hypothesized that taurine and vitamin C would restore endothelial function in young smokers by modifying monocyte-endothelial interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 34 publications
2
63
0
5
Order By: Relevance
“…23 Moreover, we cannot rule out a role of taurine in mediating anti-inflammatory effects, 60 maintaining cellular metabolism (via its effect on mitochondria), 61 and/or protection of coronary endothelium and blood flow. 62 In our murine model, taurine treatment also led to reductions in myocardial iron levels. Reduced cardiac iron levels may be related to the tonic inhibition of L-type Ca 2ϩ channels by taurine, 29,31 which is an important transferrin-independent pathway for iron transport in iron-overload conditions.…”
Section: Oudit Et Almentioning
confidence: 67%
“…23 Moreover, we cannot rule out a role of taurine in mediating anti-inflammatory effects, 60 maintaining cellular metabolism (via its effect on mitochondria), 61 and/or protection of coronary endothelium and blood flow. 62 In our murine model, taurine treatment also led to reductions in myocardial iron levels. Reduced cardiac iron levels may be related to the tonic inhibition of L-type Ca 2ϩ channels by taurine, 29,31 which is an important transferrin-independent pathway for iron transport in iron-overload conditions.…”
Section: Oudit Et Almentioning
confidence: 67%
“…The fi rst is that TA acts as an antioxidant in a dose-dependent manner (24). Through antioxidative pathways it seems to modify both target and receptor cell homeostasis (64)(65)(66). Plasma and extracellular fl uid TA concentrations typically range from 10 μmol L -1 to 100 μmol L -1 (67).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that dietary taurine showed a notable cholesterollowering effect in hypercholesterolemic rats fed a high cholesterol diet (Masuda and Horisaki, 1986;Murakami et al, 1999;Park and Lee, 1998;Hagar, 2004). It has been shown that taurine improves endothelial function and inhibits apoptosis of endothelial cell as well as decreases plasma level of LDL, which prevents initiation and progression of atherosclerosis (Fennessy et al, 2003;Murakami et al, 2002). Taurine exhibits antioxidative properties, membrane stabilizing effect, regulates intracellular Ca2+ concentration, inhibits apoptosis, reduces the levels of pro-inflammatory cytokines in various organs and controls blood pressure (Das et al, 2008;Manna et al, 2008;2009).…”
Section: Introductionmentioning
confidence: 99%